La gran madre: símbolo de lo inconsciente. Una interpretación del mito de Endimión y Selene en Cantigas de recreación, de José Basileo Acuña. - von Mayer Chaves, Peggy (2012)
This paper analizes the poem "Tercera Cantiga de Recreación: "La Gran Madre", from José Basileo Acuña's Cantigas de Recreación. Based in Endymion and Selene`s myth, the poet symbolically describes the constitutive processus of Great Mother and puer aeternus's archetypes in the realms of inconscience. The union between the young boy and Selene results in an uroboric incest, a kind of absortion toward Great Mother's lap. that shows dependency from the Ego and conscient with inconscient. Endymion, puer aeternus's archaetype doesn't reach the level of conscience and die.